“Wake Up! HIV is at Your Door”: African American Faith Leaders in the Rural South and HIV Perceptions: A Qualitative Analysis - Aholou, Tiffiany M. (Journal of religion and health, 2016)
In Alabama, 70 % of new HIV cases are among African Americans. Because the Black Church plays an important role for many African Americans in the south, we conducted qualitative interviews with 10 African American pastors recruited for an HIV intervention study in rural Alabama. Two main themes emerged: (1) HIV stigma is prevalent and (2) the role of the Black Church in addressing HIV in the African American community. Our data suggest that pastors in rural Alabama are willing to be engaged in HIV prevention solutions; more formalized training is needed to decrease stigma, strengthen HIV prevention and support persons living with HIV/AIDS.